The effect of T'ai Chi and Qigong training on patients with obstructive sleep apnea: A randomized controlled study - Yılmaz Gökmen, Gülhan; Akkoyunlu, Muhammed Emin; Kılıç, Lütfiye; Algun, Zeliha Candan (Mary Ann Liebert, Inc, 2019)
Objectives: This study aims to investigate the effects of T'ai Chi and Gigong (TCQ) training on severity of obstructive sleep apnea (OSA). Design: A prospective, 12-week, single-center, double-blinded, randomized controlled trial. Setting: Sleep Disorders Center of Medical Faculty in Istanbul, Turkey. Subjects: Fifty adult patients with mild and moderate OSA. Interventions: Patients were randomly allocated into either an intervention group or a control group. The intervention group (n=25) received TCQ training under physiotherapist supervision for 1h, three times per week, for 12 weeks and a home exercise program was provided for another 2 days. The control group (n=25) received only a home exercise program for 12 weeks, 5 days per week. Outcome measures: All patients were assessed before and after the exercise program. Objective parameters of sleep were measured by polysomnography, while subjective parameters of sleep were assessed using the Epworth Sleepiness Scale (ESS) and the 3-factor Pittsburgh Sleep Quality Index (PSQI). Pulmonary functions were assessed with a pulmonary function test; health-related quality of life was evaluated through the Short Form-36. Results: In the intervention group, there was a statistically significant decrease in the apnea-hypopnea index (AHI) (p=0.001) and percentage and duration of stage N2 sleep (p=0.041 and p=0.037, respectively), while there was a statistically significant increase in percentage and duration of stage N3 sleep when compared with the controls (p=0.048 and p=0.043, respectively). There was a statistically significant decrease in the ESS, PSQI sleep efficiency, and total scores (p=0.001, p=0.003, and p=0.003, respectively). Conclusions: Our study results suggest that TCQ training may reduce AHI and daytime sleepiness, while improving subjective sleep quality, in patients with mild and moderate OSA.
WOS: 000450066500001
PubMed ID: 30427696
Keywords: Daytime Sleepiness; Obstructive Sleep Apnea; Qigong; Sleep Quality; T'ai Chi